Modelización cartográfica mediante funciones kernel para la ubicación óptima de centros de salud mental, que requieren limeñas agredidas psicológicamente por su pareja - Kraenau Espinal y Colls., Erwin (2018)
Psychological violence, also called emotional violence, is a form of abuse; that humiliates, makes them feel bad and insecure to a person, deteriorating confidence and self-esteem; is subtle and is much more difficult to perceive or detect. It manifests itself through harsh words, insults, shouting and swearing. Various national and international organizations have advocated the elimination of violence against women in all its forms. Peru is a country of limited resources and high demand for health needs, particularly mental health services. The purpose of this research is to determine the optimal location of mental health centers that require the Lima women who are victims of psychological violence by their partner. The database used was provided by the "MIMP” Ministry of Women and Vulnerable Populations. Kernel model was applied to describe the spatial demand for mental health services required by women who suffer psychological aggression by their partner and are habitually resident in the surrounding housing for women's emergency centers located in the districts of Lima Cercado, Ate, Comas, Puente Piedra, San Juan de Miraflores, San Martin de Porres and Santiago de Surco; results indicate that mental health centers should be located in the Cercado de Lima and Santiago de Surco.